Scientific rationale for the use of special physical exercises to optimize the prelaunch conditions of highly skilled rowers in kayak and canoes - Zharmenov, D.; Khaustov, S.; Grenaderova, M. (Journal of Physical Education and Sport, 2019)
As in any other sport, in rowing and canoeing, in order to achieve high sports results, an optimal pre-start condition of the rowers is extremely important. The problem lies in the fact that rowing specialists, in particular, rowing and canoeing, do not pay enough attention in training highly qualified rowers of their pre-start readiness, and if they do, they are mainly from a psychological point of view, through psychological influence. Meanwhile, not all athletes are equally successful in psychological suggestion (influence). Therefore, the authors proposed and substantiated the positive impact of the proposed special physical exercises on the optimization of pre-start conditions of highly skilled rowers in kayak and canoes. The article presents one of the complexes of such exercises, tested in a natural pedagogical experiment, which influenced the growth of sports results in highly skilled rowers in kayak and canoes.